Protection Against Marburg Virus Using a Recombinant VSV-Vaccine Depends on T and B Cell Activation - Marzi, Andrea; Menicucci, Andrea R.; Engelmann, Flora; Callison, Julie; Horne, Eva J.; Feldmann, Friederike; Jankeel, Allen; Feldmann, Heinz; Messaoudi, Ilhem (Frontiers in Immunology, 2019)
Marburg virus (MARV) is the causative agent of hemorrhagic fever outbreaks with high case fatality rates. Closely related to Ebola virus, MARV is filamentous virus with a negative-sense, single-stranded RNA genome. Although extensive studies on filovirus countermeasures have been conducted, there are no licensed treatments against MARV infections. An experimental vaccine based on the recombinant vesicular stomatitis virus (VSV) expressing the MARV-Musoke strain glycoprotein demonstrated complete protection when a single dose is administered 28 days and up to 14 months prior to MARV challenge. Here, we analyzed the protective efficacy of an updated vaccine expressing the MARV-Angola strain glycoprotein (VSV-MARV). A single dose of VSV-MARV given 5 weeks before challenge provided uniform protection with no detectable viremia. The vaccine induced B and T cell proliferation and, importantly, antigen-specific IgG production. Transcriptomic signatures confirm these findings and suggest innate immunity engendered by VSV-MARV may direct the development of protective humoral immunity.